2003
DOI: 10.1016/j.chembiol.2003.08.008
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase Template Interactions Probed by Degenerate Isosteric Nucleobase Analogs

Abstract: The development of novel artificial nucleobases and detailed X-ray crystal structures for primer/template/DNA polymerase complexes provide opportunities to assess DNA-protein interactions that dictate specificity. Recent results have shown that base pair shape recognition in the context of DNA polymerase must be considered a significant component. The isosteric azole carboxamide nucleobases (compounds 1-5; ) differ only in the number and placement of nitrogen atoms within a common shape and therefore present u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 55 publications
0
37
0
Order By: Relevance
“…In one study, it was found that the fluorinated bases prefer to pair with themselves relative to the natural bases, similar to results seen by Kool in DNA [13, 14]. Davisson collected evidence on the roles of sterics and electrostatics in DNA synthesis using azole carboxamide base analogues [39]. McLaughlin has designed analogues lacking minor groove hydrogen bond acceptors to explore the roles of minor groove solvation in DNA stability [40].…”
Section: Why Modify Dna Bases?mentioning
confidence: 83%
“…In one study, it was found that the fluorinated bases prefer to pair with themselves relative to the natural bases, similar to results seen by Kool in DNA [13, 14]. Davisson collected evidence on the roles of sterics and electrostatics in DNA synthesis using azole carboxamide base analogues [39]. McLaughlin has designed analogues lacking minor groove hydrogen bond acceptors to explore the roles of minor groove solvation in DNA stability [40].…”
Section: Why Modify Dna Bases?mentioning
confidence: 83%
“…Azole heterocyclic carboxamides can act as nucleobase mimics and, in fact, structurally can take on the appearance of either purines or pyrimidines (Figure 6) [91]. Because these analogs are small, they have some molecular mobility and can shift in order to adjust the hydrogen bonding patterns and electronic interactions to allow pairing with different bases [91].…”
Section: Purine/pyrimidine Mimicsmentioning
confidence: 99%
“…In this design, the pyrazole-3-carboxamide was changed to a class of triazoles that include (1H)-1,2,3-triazole-4-carboxamide, (2H)-1,2,3-triazole-4-carboxamide, and 1,2,4-triazole-4-carboxamide (Figure 13B) [56]. All three analogs are rather promiscuous as each allows for the incorporation of multiple dNMPs.…”
Section: Who Needs Fidelity? Examples and Applications For The Promismentioning
confidence: 99%
“…All three analogs are rather promiscuous as each allows for the incorporation of multiple dNMPs. Of these three analogs, (1H)-1,2,3-triazole-4-carboxamide displays the highest degree of selectivity as the catalytic efficiency for incorporating dGMP is 10-fold higher than dAMP and greater than 50-fold more efficient than the incorporation of the pyrimidines dCMP or dTMP [56]. In contrast, 1,2,4-triazole-3-carboxamide and (2H)-1,2,3-triazole-4-carboxamide behave as universal nucleotides since nearly identical catalytic efficiencies are reported for the incorporation of various dNMPs.…”
Section: Who Needs Fidelity? Examples and Applications For The Promismentioning
confidence: 99%